Impact of additional floor operationalization at qualimed hospital-Iloilo a cost benefit analysis - Gasataya, Venerio G. (College of Public Health,University of the Philippines Manila, 2018)
Objective: To determine the impact of an additional floor (4th floor) operationalization at Qualimed Hospital-Iloilo. Methods: A cost analysis in the form of a Cost-Benefit Analysis (CBA) was used in this study using the With versus Without comparison scenarios. The impact of the project was evaluated based on the Benefit-to-cost Ratio (BCR), Net Present Value (NPV) analysis, Sensitivity analysis of both scenarions? quantifiable data and the added value of the qualitative residuals which were not included in NPV analysis. Results: BCR of 1.17 vs. 0.49; Net Return of 466% vs. 94%; Payback Period of 1.77years vs. 5.15 years and NPV of Php258,923,086/USD 5,178,462 vs. (Php543,434,546/USD 10,868,691) were the data comparisons of with floor expansion versus without expansion, respectiveley. The estimated benefit value of the qualitative residuals totaled to Php28,185,932.85/USD 563, 719 per month and the estimated one-time qualitative residual cost totaled to _h-485,955.40/USD 9, 719. Conclusion: Even if based on Net Return/ROI that both scenarions are attractive options, the project with 4th floor expansion is a better option and a viable investment for long-term, notwithstanding non-inclusion of the qualitative residuals net benefit valuation to the analysis.